Songs of America patriotism, protest, and the music that made a nation - Meacham, Jon 1969- (Random House, 2019)
From "The Star-Spangled Banner" to "Born in the U.S.A.," Jon Meacham and Tim McGraw take readers on a moving and insightful journey through eras in American history and the songs and performers that inspired us. Meacham chronicles our history, exploring the stories behind the songs, and Tim McGraw reflects on them as an artist and performer. Their perspectives combine to create a unique view of the role music has played in uniting and shaping a nation. Beginning with the battle hymns of the revolution, and taking us through songs from the defining events of the Civil War, the fight for women's suffrage, the two world wars, the Great Depression, the civil rights movement, the Vietnam War, and into the twenty-first century, Meacham and McGraw explore the songs that defined generations, and the cultural and political climates that produced them. Readers will discover the power of music in the lives of figures such as Harriet Tubman, Franklin Roosevelt, Eleanor Roosevelt, and Martin Luther King, Jr., and will learn more about some of our most beloved musicians and performers, including Marian Anderson, Elvis Presley, Sam Cooke, Aretha Franklin, Bob Dylan, Duke Ellington, Carole King, Bruce Springsteen, and more
Keywords: Geschichte; Amerikanismus; Song; USA; Music / Political aspects / United States / History; Music / Social aspects / United States / History; Protest songs / United States / History and criticism; Patriotic music / United States / History and criticism; Music / Political aspects; Music / Social aspects; Patriotic music; Protest songs; United States; Criticism, interpretation, etc; History